A5_10 Solar Laser - Graham, Thomas; Kaiser, Felix; Keany, Connor; Newland, Rhys; Pankhania, Kishen (Physics Special Topics, 2022)
Following on from previous work, this paper aims to demonstrate the effect on Earth’s orbit that a solar laser would have (a laser with a power equivalent to that of the Sun), ignoring all physical effects other than the radiation pressure. It is found by simulating this scenario that the Earth’s orbit is expanded at a rate of approximately 40 cm per second. A Sun powered laser is then considered, although this is found to accelerate the Earth to relativistic speeds in an extremely short timeframe.